Development of Augmented Reality-Based Learning Media on Concept of Hydrocarbon to Improve Multi-representation Ability - Vita Fitria Ningrum; Woro Sumarni; Edy Cahyono (Postgraduate, University of Mataram, 2021)
This study aims to design and develop learning media based on augmented reality on hydrocarbon material and its validity to determine the media's feasibility and increase students' multi-representation ability. This research is a type of development research using Design Research and Development (R&D). The product validity test phase was carried out by two material experts and three media experts. In addition, testing was carried out on the responses of the participating students. The implementation stage of learning was carried out by class X TKJ 2 SMK Gondang Pekalongan with a total of 32 students. The data analysis technique used a questionnaire instrument and the technical descriptive statistical analysis. The results of this study are: (1) the development of augmented reality-based learning media on hydrocarbon material in the form of an android application consisting of five main menus, namely basic competencies and indicators, materials, AR camera, practice questions, and the identity of the researcher, as well as seven molecular cards of the structure chemical compound molecules; (2) validity assessment by material experts with an average score of 85% in the